Nursing and Midwifery Students\' Knowledge and Attitudes Regarding Children\'s Pain - John Bright Agyemang; Abigail Kusi-Amponsah Diji; Richard Adongo Afaya; Hanson Boakye; Evans Oduro; Albert Amagyei; Joana Kyei-Dompim (Golestan University of Medical Sciences, 2020)
Background: The knowledge and attitudes of nurses and midwives, as well as nursing and midwifery students on pediatric pain are crucial in the management of hospitalized children's pain. However, few studies have addressed the preparedness of nursing and midwifery students to manage children's pain based on their knowledge and attitudes. This study therefore assessed nursing and midwifery students' knowledge and attitudes pertaining to children's pain management. Methods: This descriptive cross-sectional study was conducted on 554 nursing and midwifery students who were in their last year at four nursing and midwifery training institutions in city Ghana in 2018-2019. Data were collected over a three-month period using the Pediatric Nurses' Knowledge and Attitudes Survey regarding pain (PNKAS). Data analyzed by the SPSS version 25 and presented using descriptive statistics and independent T test and one-way ANOVA. Results: Participants had an average PNKAS score of 42.1% (range: 21.4% to 81.0%). The nursing and midwifery students in either public (44.1%±7.9%) or private (43.7%±9.6%) university had significantly higher scores than those in a public nursing and midwifery training college (40.3%± 6.9%) (p<.001). Conclusion: Nursing and midwifery students in the study generally had insufficient knowledge and attitudes toward children's pain. There is an urgent need to intensify education in this area so as to adequately prepare these students to cater to the pain needs of vulnerable children and their families. Future studies should focus on how student's theoretical knowledge and attitudes are linked to their pediatric pain assessment and management practices.